Concordance between Experiences of Bereaved Relatives, Physicians, and Nurses with Hospital End-of-Life Care: Everyone Has Their "Own Truth". (5th April 2015) - Witkamp, F. E.; van Zuylen, L.; Vergouwe, Y.; van der Rijt, C. C. D.; van der Heide, A.
Abstract : When patients die relatives and healthcare professionals may appreciate the quality of the dying phase differently, but comparisons are rare. In a cross-sectional study (June 2009–July 2012) the experiences of bereaved relatives, physicians, and nurses concerning the quality of dying in a large Dutch university hospital were compared, and the relation to communication was explored. Measurements were concordance on the quality of dying (QOD) (0–10 scale), awareness of impending death, and end-of-life communication. Results . Data on all three perspectives were available for 200 patients. Concordance in general was poor. Relatives' scores for QOD (median 7; IQR 5–8) were lower than physicians and nurses' (both median 7; IQR 6–8) (P = 0.002 ). 48% of the relatives, 77% of the physicians, and 73% of the nurses had been aware of impending death. Physicians more often reported to have informed patients and relatives of end-of-life issues than relatives reported. When both physicians and relatives reported about such discussion, relatives' awareness of impending death and presence at the patient's deathbed were more likely. Conclusion . Relatives, physicians, and nurses seem to have their "own truth" about the dying phase. Professionals should put more emphasis on the collaboration with relatives and on verification of relative's understanding.